Perceptions of cell-cultured “meat” embedded in the cultural context: public surveys in Japan and the United Kingdom - Hibino, Aiko (Frontiers in Nutrition, 2026)
The labeling of cell-cultured products for food application as “meat” remains contentious, with public perceptions varying across cultural contexts. This study examined how individuals in Japan and the United Kingdom (UK) perceive cell-cultured products, particularly whether they should be called “meat.” An online survey was conducted with 1,200 respondents aged 20–59 years (600 in Japan and 600 in the UK). The questionnaire included items on agreement with calling cultured products as “meat,” willingness to try cultured meat, images associated with meat, views on life, dietary patterns, and interest in environmentally friendly foods. Multiple correspondence analyzes were performed to identify clusters of opinions. Respondents interested in environmentally friendly food were more likely to support labeling cultured products as “meat” and to express willingness to try them. In Japan, those who have the relational view on life were more likely to show strong willingness to try cultured meat, whereas in the UK, vegetarian respondents were more likely to reject it. The categorical boundaries for ambiguous cell-cultured products are co-occurring with a globally expanding framework of environmental consciousness; however, attitudes are also shaped by culturally specific factors, as demonstrated in Japan and the UK. These findings underscore the importance of cultural context in guiding communication.